O menino com cabeça de urubu: processos de recategorização multimodal em Castanha do Pará, de Gidalti Jr. - Alfonso Junior, Flavio [UNIFESP] (2019)
The main objective of this work is to investigate and analyze the multimodal recategorization processes that occur in the comic book Castanha do Pará, by Brazilian author Gidalti Jr. We chose to focus on the introduction and the transformations – activated through verbal and nonverbal elements – through which, throughout the narrative, the main character of the book, the boy Castanha, goes through, as well as the ways in which such processes contribute to the construction of meanings in the work. Thus, we seek to develop this work through theoretical supports of Textual Linguistics (LT), socio-cognitive-interactional (more specifically, referencing and recategorization), among them Koch (2004), Koch and Marcuschi (1998), Koch and Elias (2016), Cavalcante (2003, 2005, 2011, 2012) and Mondada and Dubois (2003). From the assumptions of LT, we will be linked to the paths that integrate multimodality and referencing, outlined by Lima (2017), Capistrano Júnior (2012), Custódio Filho (2011) and Ramos (2007, 2012). To address issues of image and its relations of cohesion and meaning, and more specifically comics, we will seek the theoretical proposals of Barthes (1990) and Ramos (2011). As a result of the work, we verified that the character Castanha is recategorized and assumes different traits during the course of the book, marked by the variation between maintenance and transformation of the referent, both via verbal and nonverbal elements. In addition, it is clear that verbal and nonverbal elements act concomitantly for the construction of the character and its symbologies, as well as for the development of the narrative.